Program Electronic Word of Mouth di Shopee dengan Minat Beli Konsumen - Muhammad Alif Alfasyah; O. Hasbiansyah (Bandung Conference Series: Communication Management, 2022)
Abstract, The rapid progress of the internet makes business people rack their brains on how to take advantage of this progress into something profitable. Electronic word of mouth is one way for business people to take advantage of the advancement of the internet in marketing their products. In electronic word of mouth there are several dimensions, namely, intensity, valence of opinion, and content. One of the e-commerce that is the focus of this research is Shopee. The purpose of this study was to determine whether there is a relationship between the electronic word of mouth program at Shopee and consumer buying interest, therefore this study uses marketing communication theory. The method used in this study is the correlation method, and the sampling technique used is quota sampling with 100 respondents. The result of this research is that there is a relationship between the electronic word of mouth program at Shopee and consumer buying interest. Abstrak, Pesatnya kemajuan internet membuat para pebisnis memutar otak bagaimana memanfaatkan kemajuan tersebut menjadi sesuatu yang menguntungkan. Electronic word of mouth merupakan salah satu cara bagi para pelaku bisnis untuk memanfaatkan kemajuan internet dalam memasarkan produknya. Dalam electronic word of mouth terdapat beberapa dimensi yaitu, intensitas, valensi pendapat, dan isi. Salah satu e-commerce yang menjadi fokus penelitian ini adalah Shopee. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada hubungan antara program electronic word of mouth di Shopee dengan minat beli konsumen, oleh karena itu penelitian ini menggunakan teori komunikasi pemasaran. Metode yang digunakan dalam penelitian ini adalah metode korelasional, dan teknik pengambilan sampel yang digunakan adalah quota sampling dengan jumlah responden 100 orang. Hasil dari penelitian ini adalah terdapat hubungan antara program electronic word of mouth di Shopee dengan minat beli konsumen.